Patterns in foodgrain consumption and calorie intake - Berhane, Guush; McBride, Linden; Hirfrfot, Kibrom Tafere; Tamru, Seneshaw (University of Pennsylvania Press, 2012)
The quality, quantity, and composition of food consumption are major determinants of the nutritional well-being of individuals, which has, in turn, important implications for individual and household-level health, productivity, and income. An analysis of food consumption patterns is essential to understanding and projecting domestic demand for agricultural products, as well as for the development of national policies to promote food security.